COGNITIVE AND PHYSIOLOGICAL INITIAL RESPONSES DURING COOL WATER IMMERSION - Alex Buoite Stella; Cornelis Peter Bogerd (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2014)
The initial responses during water immersion are the first mechanisms reacting to a strong stimulation of superficial nervous cold receptors. Cold shock induces tachycardia, hypertension, tachypnea, hyperventilation, and reduced end-tidal carbon dioxide fraction. These initial responses are observed immediately after the immersion, they last for about 3 min and have been also reported in water temperatures up to 25 °C. the aim of the present study was to observe cognitive and physiological functions during immersion in water at cool temperature. Oxygen consumption, ventilation, respiratory frequency, heart rate and expired fraction of oxygen were measured during the experiment. A code substitution test was used to evaluate executive functions and, specifically, working memory. This cognitive test was repeated consecutively 6 times, for a total duration of 5 minutes. Healthy volunteers (n = 9) performed the test twice in a random order, once in a dry thermoneutral environment and once while immersed head-out in 18 °C water. The results indicated that all the physiological parameters were increased during cool water immersion when compared with the dry thermoneutral condition (p < 0.05). Cognitive performance was reduced during the cool water immersion when compared to the control condition only during the first 2 min (p < 0.05). Our results suggest that planning the best rescue strategy could be partially impaired not only because of panic, but also because of the cold shock.